Marketing Strategy to Increase Sweembath Bathrooms Village, Soppa, Bandar Huluan District, Simalungun District - Amlys, Amlys Syahputra Silalahi; Hariadi , Hariadi Susilo; Dardanila, Dardanila; Saib , Saib Suwilo; Eva, Eva Sartini Bayu; Ma'ruf, Ma'ruf Tafsin; Peni, Peni Patriani; Tugiman, Tugiman; Farida , Farida Ariani; Ainun, Nur'ainun (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The Sweembath Tour of Naga Soppa Village has long been known by tourists, both the local community and tourists who come from Medan, Asahan, Labuhan Batu and Samosir. The Sweembath Bathing Site in Naga Sopa Village, Bandar Huluan District, Simalungun Regency has an attraction where the water comes from natural springs, water clarity and natural beauty which was once a place for recreation or bathing for Dutch citizens during the colonial era. However, in its development, the Sweembath Tour of Naga Soppa Village experienced ups and downs. Therefore, it is necessary to plan a marketing strategy to increase tourism visits to the Sweembath Naga Soppa Village baths. The marketing strategy that can be done through a marketing mix strategy. The Marketing Mix Strategy consists of product, price, promotion and distribution strategies which in its application is expected to increase the desired response from the target market so that it will determine the success of marketing. This marketing mix uses the 4Ps, namely: Product is something that can be offered to the market in the form of physical goods or services. Price is an amount of money spent by consumers to buy the products or services offered. Place is a distribution channel for selected products and services to be delivered to customers and consumers. while Promotion is an activity from producers to introduce products or services produced to consumers